Differential diagnosis of sporotrichosis and cutaneous leishmaniasis: Case report (Research, Society and Development, 2025)
Cutaneous leishmaniasis (TL) and sporotrichosis are two cutaneous-subcutaneous infections that can overlap clinically. Both cause chronic skin lesions that sometimes follow the lymphatic vessels, but have distinct agents, transmission routes, laboratory findings, and therapeutic approaches. The objective of this study is to report a case on the differential diagnosis between leishmaniasis and sporotrichosis, highlighting the importance of fungal culture in the diagnosis of the lesion for proper treatment and prevention of future complications. This case report aims to demonstrate the clinical, epidemiological, and histological differences between leishmaniasis and sporotrichosis, as seen in the stages described in this study. According to the studies, distinguishing between these pathologies is important, as they have different treatments, and correct treatment helps prevent future complications. With appropriate treatment, most cases of both diseases have a good outcome; however, there are risks. Therefore, it is essential to carry out a detailed description of the lesions and correlate them with clinical and epidemiological data, in addition to specific complementary tests of cultures, direct research and anatomopathology.